Alternative ways of classifying river water quality using chemometric methods - Low, K.L.; Zain, Sharifuddin Md (2005)
Variables used by DOE to calculate the water quality index (WQI) in classifying rivers are the chemical oxygen demand (COD), biochemical oxygen demand (BOD), ammoniacal nitrogen (AN), suspended solid (SS), dissolved oxygen (DO) and pH (PH). In this work, we focus on the use of principal component analysis (PCA) and multiple linear regression (MLR) as an alternative classification method. 2D PCA results do not exhibit clear linearly separable classes but 3D plot incorporating PC3 results in better clustering. The clusters still overlap but classification can be made though rather contentious. MLR on the other hand is seen to be able to predict the WQI reasonably well.